Integrative Physiotherapy Approaches for Sacroiliac Joint Dysfunction: Efficacy of Ultrasound, Ventral Glide Mobilization, and Lumbopelvic Rotation Mobilization - Tiar Erawan; L Sri Saadiyah; Rahmat Nugraha; Andi Halimah; Muhammad Nuralamsyah; Agussalim (Journal of Pharmacy and Bioallied Sciences)
Background: Sacroiliac joint dysfunction is a complaint of pain in the buttocks area that causes limited sacroiliac joint mobility. Aim: To determine the management of physiotherapy in sacroiliac joint dysfunction. Material and Method: 2 patients were evaluated with data collection through pain measurement using a Visual Analog Scale (VAS) and functional ability measurement using Five-Time Sit-to-Stand (FTSTS). Result: We found that the diagnosis of pain and functional movement limitations was due to Sacroiliac Joint Dysfunction. Conclusion: Therefore, the management of physiotherapy with ultrasound therapy, ventral glide mobilization Kalternborn, and lumbopelvic rotation mobilization can result in a decrease in muscle pain and spasms, as well as an increase in functional ability.